1990
DOI: 10.1111/j.1740-8261.1990.tb00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐skeletal Distribution of Bone‐seeking Radiopharmaceuticals

Abstract: A variety of factors may change the normal distribution of bone‐seeking radiopharmaceuticals. This paper presents a classification of non‐skeletal bone tracer distribution according to physiologic, pathologic, and artifactual causes. The mechanisms thought to account for non‐skeletal distribution are reviewed. Examples of non‐skeletal bone tracer distribution include calcinosis cutis and pulmonary mineralization in hyperadrenocorticism, renal infarct, acute rhabdomyolysis, urine contamination, lymph node uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Phagocyte‐mediated fragmentation of degenerating muscle fibers peaks in 3–4 days 5 . Bone tracer uptake correlates with local tissue Ca 2+ concentration and involves adsorption to microscopic calcium and degraded macromolecules 1,26–29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phagocyte‐mediated fragmentation of degenerating muscle fibers peaks in 3–4 days 5 . Bone tracer uptake correlates with local tissue Ca 2+ concentration and involves adsorption to microscopic calcium and degraded macromolecules 1,26–29 …”
Section: Discussionmentioning
confidence: 99%
“…5 Bone tracer uptake correlates with local tissue Ca 2 þ concentration and involves adsorption to microscopic calcium and degraded macromolecules. 1,[26][27][28][29] The disparity in interrater agreement of focal uptake between the orthogonal views was not expected. Interrater agreement for lateral images (k ¼ 0.65) was higher than that for caudal images (k ¼ 0.26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D ystrophic mineralization of soft tissues is a common feature in dogs with Cushing's syndrome. [1][2][3][4][5][6][7] Results from postmortem studies in dogs with Cushing's syndrome have shown that dermal mineralization occurs in 40% of the dogs and pulmonary interstitial mineralization can be detected microscopically in 90% of the dogs. 1 A previous report described a dog with idiopathic Cushing's syndrome and interstitial pulmonary mineralization.…”
mentioning
confidence: 99%
“…6 Additionally, pulmonary uptake of 99m Tc-methylene diphosphonate ( 99m Tc-MDP) in a dog with Cushing's syndrome has been described. 7 Four dogs with pituitary-dependent hyperadrenocorticism (PDH) and pulmonary interstitial mineralization based on thoracic radiographic changes or delayed bone phase scintigraphy using 99m Tc-MDP with normal pulmonary 99m Tc-macro-aggregated albumin ( 99m Tc-MAA) perfusion scintigrams have been described. 8 In the 2 dogs studied with 99m Tc-MDP, the intensity of uptake was greater than surrounding bone uptake.…”
mentioning
confidence: 99%